Enhancement of liquid phase adsorption column performance by means of oscillatory flow: an experimental study - Lau, A; Crittenden, B; Field, R (2004)
Oscillations have been applied to the bulk fluid flowing upwards through a column packed with spherical beads of 3A zeolite that is used to dry an ethanol solution containing about 3.2 wt.% water. For a given bulk flow rate, concentration and temperature of the feed, the application of oscillations leads to a delay in the breakthrough time and a sharper breakthrough curve than for the case when there is no oscillation. Use of oscillatory flow, therefore, leads to an increased bed capacity up to the point of breakthrough, a lower length of unused bed and a reduced mass transfer zone length (MTZL). Improvements in all these parameters of up to 20% have been found for oscillations with frequencies up to 2.4 Hz and amplitudes up to 0.001 m. The best improvements were found for the highest frequencies and amplitudes that could be achieved with the apparatus. In the development of the process it is believed that a further 20-30% improvement could realistically be achieved. However, practical limitations to the upper bounds of these two oscillatory parameters arise from the strength of the adsorbent particles and the risk of movement of particles within the bed. The main reason for the improvement in the process, when oscillations are applied, is the increase in interparticle transport. The increase in interparticle heat transfer is potentially as relevant as that in interparticle mass transfer. The results obtained for this model chemical system show that process improvements through the use of oscillatory flow can be obtained with well-rounded particles and it is speculated that the method could be applicable more generally to all liquid phase adsorption processes. © 2003 Elsevier B.V. All rights reserved.